1 D Hierarchical MnCo2O4 Nanowire@MnO2 Sheet Core–Shell Arrays on Graphite Paper as Superior Electrodes for Asymmetric Supercapacitors. Issue 8 (19th November 2015) - Liu, Shude; Hui, Kwan San; Hui, Kwun Nam
Abstract: Heterostructured metal oxide core–shell architectures have attracted considerable attention owing to their superior electrochemical performance in supercapacitors compared to a single structure. Here, we report a simple and effective synthesis of hierarchical MnCo2 O4 nanowire@MnO2 sheet core–shell nanostructures anchored on graphite paper for use in supercapacitors. The proposed electrode exhibits a specific capacitance of 2262 F g −1 at 1 A g −1 . In addition, good rate capability and excellent cycling performance are observed. An asymmetric supercapacitor with operating potential at 1.6 V is demonstrated using MnCo2 O4 @MnO2 as cathode and graphene/nickel foam (NF) as anode. The MnCo2 O4 @MnO2 //graphene/NF asymmetric device shows a high energy density of 85.7 Wh kg −1 at a power density of 800 W kg −1 while maintaining a high energy density of 34.7 Wh kg −1 at 24 kW kg −1 . Moreover, the device demonstrates a long‐term cycling stability of 81.6 % retention of its initial specific capacitance. Abstract : Rational design of hierarchical core–shell architectures of metal oxides is essential for achieving high electrochemical performance. This article describes a simple and effective synthesis of hierarchical MnCo2 O4 nanowire@MnO2 sheet core–shell nanostructures anchored on graphite paper for high‐performance supercapacitors.